Cellulase-Assisted Extraction, Characterization, and Bioactivity against Rheumatoid Arthritis of Astragalus Polysaccharides - Ling Cao; Mi Yu; Chonghui Wang; Yunhui Bao; Minghui Zhang; Ping He; Yan Zhang; Tingting Yang; Lulu Li; Gang Li; Yun Gong (International Journal of Polymer Science)
This study investigated the effect of cellulase on the isolation of crude Astragalus polysaccharide (APS), analyzed the monosaccharide component of deproteinized APS, detected the molecular weights of purified APS, and examined the biological activities and the preliminary mechanism against rheumatoid arthritis (RA). Compared with water extraction method, cellulase-assisted extraction increased the yield of crude APS to 154% and polysaccharide contents to 121%. Crude APS was then purified by ethanol precipitation, Sevag deproteinization, and high-performance liquid chromatography (HPLC) analysis; monosaccharide contents of APS were different after cellulase-assisted method, especially galacturonic acid content which significantly increased. DEAE-52 cellulose column chromatography isolated three polysaccharide fractions, including a neutral polysaccharide (APS-water) and two acidic polysaccharides (APS-NaCl1 and APS-NaCl2). Using high-performance gel permeation chromatography (HPGPC), the molecular weights of APS-water, APS-NaCl1, and APS-NaCl2 were identified as 67.7 kDa, 234.1 kDa, and 189.4 kDa, respectively. Then their therapeutic effects and possible mechanism against RA were explored using type II collagen-induced arthritis (CIA) rat model. APS could significantly reduce paw swelling, serum concentration of IL-1β and TNF-α, and the expression levels of NF-κB-p65 and IκBα in synovial membranes in CIA rats. Our study indicated that cellulase significantly increases the yield and polysaccharide contents of crude APS, improves the product quality, and preserves the biological features against RA in CIA rats.